Klebsormidin A and B, Two New UV-Sunscreen Compounds in Green Microalgal Interfilum and Klebsormidium Species (Streptophyta) From Terrestrial Habitats - Hartmann, Anja; Glaser, Karin; Holzinger, Andreas; Ganzera, Markus; Karsten, Ulf (Frontiers in Microbiology, 2020)
The terrestrial green algal members of the genera Interfilum and Klebsormidium (Klebsormidiophyceae, Streptophyta) are found in biological soil crusts of extreme habitats around the world where they are regularly exposed, among other abiotic stress factors, to high levels of ultraviolet radiation (UVR). As a consequence those species synthesize and accumulate either one or two mycosporine-like amino acids (MAAs), whose chemical structure was unknown so far. In the present study both MAAs were isolated and structurally elucidated. The two new compounds exhibit absorption maxima of 324 nm. MAA 1 has a molecular weight of 467 and MAA 2 of 305, and the latter (MAA 2) could be identified as N-(4,5-dihydroxy-5-(hydroxymethyl)-2-methoxy-3-oxocyclohex-1-en-1-yl)-N-methylserine using one- and two-dimensional 1H and 13C-NMR spectroscopy. MAA 1 contains an additional sugar moiety. As trivial names for these two novel MAAs we suggest klebsormidin A and klebsormidin B. Different species from all previously described phylogenetic clades of Klebsormidiophyceae were chemically screened for their MAA composition in aqueous extracts using RP‐HPLC and LC‐MS. The novel klebsormidin A was present throughout all clades and hence could be suitable as a chemotaxonomic marker. Additionally, controlled UVR‐exposure experiments with all investigated species showed that MAA formation and accumulation can be strongly induced by short wavelengths, supporting the role of these compounds as natural UV‐sunscreen as well as explaining the cosmopolitan distribution and ecological success of Interfilum and Klebsormidium in terrestrial habitats.